Policy diffusion, lobbying and the taxation of emissions - Peter Michaelis; Thomas Ziesemer (Universität Augsburg, Institut für Volkswirtschaftslehre, 2008)
Policy diffusion refers to the process by which a political innovation like the introduction of a novel emission tax disseminates over time among countries. In order to analyze this issue from an economic point of view we develop a simple two-country-model of the taxation of emissions in presence of (possible) policy diffusion. Contrary to the usual Nash setting of simultaneous decision making we consider a Stackelberg game: In the first step the domestic government introduces an emission tax td thus acting as Stackelberg-leader, in the second step the foreign government decides whether or not to introduce an emission tax tf and in the third step the firms decide on their output quantities to be sold on a third country's market. For the case of an exogenous given probability of policy diffusion we show that the optimal domestic tax rate is c.p. the higher, the higher the probability of policy diffusion is. Moreover, we explore under which conditions first-mover behaviour by the domestic government leads to a higher tax rate compared to the Nash solution In the next step we introduce an endogenous probability of policy diffusion by combining our model with a strategic lobbying approach. As a result, the probability of policy diffusion is c.p. the smaller, the higher domestic tax rate td is. Consequently, in fixing the optimal tax rate the domestic government has to account for the foreign firm's lobbying activities otherwise it will choose a tax rate too high
urn:nbn:de:bvb:384-opus4-711310
Keywords: F18; Q55; Q58; 330; emission taxes; first-mover behaviour; strategic environmental policy; policy diffusion